Comparative analysis of three human adipocyte size measurement methods and their relevance for cardiometabolic risk. Issue 1 (24th November 2016) - Laforest, Sofia; Michaud, Andréanne; Paris, Gaétan; Pelletier, Mélissa; Vidal, Hubert; Géloën, Alain; Tchernof, André
Abstract : Objective: To determine whether adipocyte diameters from three measurement methods are similarly associated with adiposity measurements and cardiometabolic variables. Methods: Surgical samples of omental and abdominal subcutaneous adipose tissue were obtained in a sample of 60 women (age 35–59 years; body mass index 20.3–41.1 kg/m 2 ). Median adipocyte diameter of the main cell population was determined by collagenase digestion, osmium tetroxide fixation, and histological analysis. Adiposity and cardiometabolic risk factors were assessed. Results: Adipocyte diameter was consistently smaller with formalin fixation than with collagenase digestion, whereas osmium‐fixed cells were larger ( P < 0.0001, for all). Median adipocyte diameters derived from all methods were intercorrelated ( r = 0.46–0.83, P < 0.001 for all). Positive associations were found between adipocyte diameters from all techniques and regional or total adiposity measurements ( P < 0.01 for all). Omental adipocyte diameter was positively associated with fasting glucose, insulin, and homeostatic model assessment of insulin resistance ( r = 0.30–0.52, P < 0.05 for all), with osmium‐fixed cell size as a stronger correlate. Osmium‐fixed cell diameter was also a better correlate of plasma adiponectin and leptin. Conclusions: Although measurement techniques generated systematic differences in adipocyte size, associations with adiposity were only slightly affected by the technique. Osmium fixation generated stronger associations with cardiometabolic risk factors than collagenase digestion and histological analysis.